A systematic review on the psychological factors behind vaccine hesitancy in the COVID-19 era - Panico, Francesco; De Biase, Rosalia; Catalano, Laura; Zappullo, Isa; D'Olimpio, Francesca; Trojano, Luigi; Sagliano, Laura (Frontiers in Public Health, 2025)
BackgroundVaccine hesitancy may represent a global threat because of its inherent consequences for health, social and economic systems. Understanding the factors associated with vaccine hesitancy is fundamental to developing effective healthcare policies. While previous studies have mainly focused on sociological and cultural variables and transient illness-specific fears and beliefs, the present systematic review focuses on the psychological factors (such as emotional dispositions, cognitive functioning and expectations, and stable personality traits) associated with vaccine hesitancy during the COVID-19 era.MethodsA systematic review using a systematic search of PubMed, PsychINFO and Web of Science databases was performed with a time frame ranging between 1 January 2020 to 31 January 2025 focusing on psychological factors and vaccine hesitancy. Studies targeting the general population and employing validated instruments to assess emotional, cognitive and personality factors and vaccine hesitancy were selected, while investigations on context-specific, psycho-social, cultural and political factors were excluded. Quality and risk of bias in the selected studies was assessed using an adapted version of the Newcastle-Ottawa Scale, and main studies’ characteristics, variables and outcomes were synthesised using a narrative approach and table.ResultsFourteen studies were finally included in the qualitative synthesis. The results showed that some variables such as depressive and anxiety levels, as well as emotion regulation strategies may affect vaccination behaviour, although some cultural and generational differences were also observed. Differences in cognitive flexibility, decision-making, and personal expectations may influence vaccine hesitancy. Notably, some personality factors, like extraversion, openness, conscientiousness and dark personality traits, may influence hesitancy to vaccinate.ConclusionThis review highlights emotional, cognitive, and personality factors associated with vaccine hesitancy, providing evidence for personalised, evidence-based interventions aimed at promoting adherence to national vaccination policies.